Hiring preferences of small and medium scale enterprises in Iloilo City - Conanan, Jean G.; Iguban, Jean M.; Malazarte, Ma. Lira L.; Patricio, Riza P.; Relimbo, Catharine R. (2003.)
This study focused on the hiring preferences of Small and Medium Enterprises in Iloilo City. Basically, it aims to answer the following questions: 1) What are the recruitment/hiring policies of SMEs in Iloilo City? ; 2) What other qualifications do SME require? [ 3) What are the types of examination given? ; and 40 all things equal, does the institution where the applicants graduated really matters? In order for these questions to be answered, the researchers distributed questionnaires to 50 SMEs based in Iloilo City. This study used a descriptive analytical design. The result of this research showed that the hiring preferences of SMEs differ from one company to another. But generally, SMEs preferred applicants with good personality. This was the first priority or consideration that they exercise when hiring. It is followed by work experience, interview rating, academic performance, age, religion and sex, relationship with employer and result of examination.
[Research Paper] (Mgt 199-Management Research). -- [Iloilo City : University of the Philippines in the Visayas - College of Management], Second Semester SY 2002-2003.